‘Here I Stand’: Paul Robeson on Adult Education as Cultural Work, Pan-Africanism and Socialist Persuasion - Stephen Brokfield (Adult Education Research Conference, 2006)
This paper explores adult educational dimensions of the work of Paul Roberson the acclaimed athlete, singer, actor, linguist and political activist.
Keywords: Paul Robeson; cultural work; Pan-Africanism; socialism